On Uncertainty and Uncertainty Reduction - Ugo Corte (Sociologica)
This essay introduces a Debate Section of Sociologica discussing Patrik Aspers’ book Uncertainty: Individual Problems and Public Solutions (Oxford University Press, 2024). It delineates the differences between risk and uncertainty as well as between individual means to reduce uncertainty and public ways of reducing uncertainty.